Rangamandapa (open type of pillared hall) - Temples of India Project Team (Jio Institute, 2024)
The rangamandapa (open type of pillared hall) is comprised of a multitude of heavy, ornately carved pillars that support the ceiling, crafted in two distinct styles. The outer pillars feature a square base which turns into faceted shapes and transitions into a circular shaft. in contrast, the innermost pillars maintain a square shape and display depictions of deities on the panels at the top, supporting the brackets. There is a Shiva linga at the centre of the hall.